RSM Modelling and Optimization of CO2 Laser Machining of Industrial PVC Foam - Sivarao, Subramonian; Robert, Milkey; Samsudin, Abdul Rahim (Praise Worthy Prize, 2013)
This paper presents a response surface methodology (RSM) in establishing an optimized model to perfectly cut an industrial PVC foam using CO2 laser machine. The influence of cutting speed, laser power, frequency, duty cycle and gas pressure on kerf width has been considered in this investigation. Identification of the important parameter effects presented using analysis of variance (ANOVA) technique combined with graphical representation which provides a clearer picture of the whole laser profiling phenomenon. A predictive mathematical model was then developed through regression analysis to study the response, namely kerf width. It was demonstrated that, the RSM has played a valuable role to identify the interaction factors of design parameters in attaining industrial desired cut quality response.